Low–Harmonic Control Strategy of a Dual Three–Phase Synchronous Reluctance Motor Based on Three–Vector Synthesis - Huang, Yonghong; Liu, Yihang; Wang, Qicuan; Yang, Fan (Energies (Basel), 2022)
Dual three–phase synchronous reluctance motors (DTP–SynRM) have the advantages of simple structure, high power density, fast dynamic response, and small torque ripple, and have broad application prospects in flywheel batteries. However, the synchronous reluctance motor has no permanent magnet, and the inductance value will change with the current change in actual operation. Direct torque control (DTC) is more suitable for the control strategy of dual three–phase synchronous reluctance motors because of its low dependence on motor parameters. However, traditional direct torque control uses a large vector control motor within one control period, which can not suppress the inherent 5th and 7th current harmonics in the motor. A new harmonic suppression method is proposed in this paper: that is, using a low harmonic vector to replace a large vector in traditional direct torque control, which can be synthesized by adjusting the action time and order of three adjacent large vectors within one control period. Through this improvement, torque control can have a harmonic suppression effect. The three vector synthesis method can make full use of the existing space voltage vector, and to adapt to different working conditions, two synthesis methods of switching frequency reduction and constant torque response are proposed. An improved direct torque control strategy is obtained by optimizing the design of the switch table using a new vector synthesis method. Finally, the suppression effect of traditional DTC and improved DTC on current harmonics is compared and analyzed. The results show that the direct torque control with low harmonic vector can suppress the harmonic current in x–y subspace, and the current harmonic content is greatly reduced.